Cysteine synthase (O-acetylserine (thiol) lyase) substrate specificities classify the mitochondrial isoform as a cyanoalanine synthase - Warrilow, A G (Journal of experimental botany, 2000)
A cyanoalanine synthase and two isoforms (A, cytosolic and B, chloroplastic) of cysteine synthase (O:-acetylserine (thiol) lyase) were isolated from spinach. N-terminal amino acid sequence analysis of the cyanoalanine synthase gave 100% homology for the determined 12 residues with a published sequence for the mitochondrial cysteine synthase isoform. All three enzymes catalysed both the cysteine synthesis and cyanoalanine synthesis reactions, although with different efficiencies. Michaelis-Menten kinetics were observed for all three enzymes when substrate saturation experiments were performed varying O:-acetylserine, chloroalanine and cysteine. Negative co-operative kinetics were observed for cysteine synthases A and B when substrate saturation experiments were performed varying sulphide and cyanide, compared with the Michaelis-Menten kinetics observed for cyanoalanine synthase. The exception was negative co-operativity observed towards sulphide for cyanoalanine synthase with O:-acetylserine as co-substrate. The optimum sulphide concentration was dependent on the alanyl co-substrate used. The amino acid sequence similarity places these three enzymes in the same gene family, and whilst the close kinetic similarities support this, they also indicate distinct roles for the isoforms